ANALISIS KUALITAS BUTIR SOAL UJIAN NASIONAL MATA PELAJARAN MATEMATIKA SEKOLAH MENENGAH PERTAMA - Riduan Yusuf (Mahesa Research Center, 2020)
This study aims to determine the level of difficulty, differentiation, and effectiveness of Deception Options of the National Examination Mathematics Subject for Junior High School/MTs Academic Year 2017/2018. This research is a quantitative study with descriptive analysis method. The population in this study is student class IX of two schools, namely: SMP MMA UISU and MTs Al Manar totaling 144 people and the sample in this study was 57 multiple choice answer sheets. Data collection method was the method of observation and tests. This research instrument was in the form of a multiple choice package of National Examination Mathematics Subject for Junior High School/MTs Academic Year 2017/2018along with the answer key lessons covered by 40 questions. Analysis conducted using the Anates 4.0.9.The result of this study is obtained the quality of the items namely (1) at SMP MMA UISU, 20 items of good quality, 12 items of good enough quality, 8 items of bad quality (2) at MTs Al Manar, 26 items of good quality, 7 items of good enough quality, 7 items of bad quality.